Fundas biflex y su efecto en la calidad del fruto de banano (Musa spp.) clon Valery. - Vera Castillo, Freddy Javier (2015)
The research was conducted at Hacienda Envy owned Noboa Group located in the canton Quevedo, province of Los Rios, whose geographical coordinates are 0° 52' 24" south latitude and 79° 23' 80" west longitude at an altitude 73 m with a duration of 120 days. The objective was to evaluate the effect of the sheath Biflex xp on fruit quality of banana (Musa spp.) Clone Valery for which a design is applied completely randomized (CRD) with 4 treatments and 4 repetitions, using 10 plants per Repeat. All variables were subjected to analysis of variance to measure the differences between treatment means the Tukey test was used at 5% probability. The treatment T1 (Biflex xp) gets the highest average by scar growth and increased 1.62 percentage declines to 10%; also it shows the best results for the variable ratio, long fingers and exportable fruit crates 1.55, 25.10 cm and 30.25 kg, likewise; It presents the best benefit with a profit of $ 5.10 and the best cost / benefit ratio with a margin of 1.17; T2 treatment (Biflex xp + 1 diaper) is better bunch weight (kg), number of hands and fingers level of treatment with a bunch weight of 34.78 kg, 9.28 and 44.45 degrees hands thick finger also has the highest average per damage point 1.84; T3 (Biflex xp + 2 diapers) treatment has the lowest rate of wastage by scar 1.47 and the lowest percentage of losses 9% and T4 (+ buprofesina Bifenthrin) presented treatment declines by 1.24 point damage..